The effects of drying method and temperature on the nutritional quality of watermelon rinds - Sanwiriya, P.; Suleiman, Norhidayah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
The present work was aimed to investigate the effect of drying methods (oven drying, foam mat drying) and temperatures (40°C, 60°C) on the nutritional characteristics of red- and yellow-watermelon rinds. It was found that foam mat drying produced the best results for preserving the most nutrients as compared to the conventional oven drying for both red- and yellow watermelon rinds. Temperature is a significant parameter that affects the nutritional characteristics of watermelon rinds powder for both methods. Finding suggests that foam mat drying at 40°C was the best method for producing watermelon rinds powder as it requires shorter treatment time and gave the best retention of protein and carbohydrate.